STRATEGI KOMUNIKASI PEMASARAN JULIAN.CLO MELALUI PENGGUNAAN INSTAGRAM DALAM MENINGKATKAN PENJUALAN - Fitria (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
The number of distribution outlets in Palu City itself is increasing and are competing in various ways to market their products. Julian.clo takes a new breakthrough by using celebgram as a medium for spreading marketing messages. The type of researcher used is a qualitative type. The basis of the research in this study is a case study with a sampling method of determining the number of people, the data collection technique used is in-depth interviews. The data analysis technique used is qualitative data analysis techniques. The results showed that the Goal setting strategy, Audience mapping, Content ideation and planning, Content Creation, Content distribution, Content amplification, Content marketing evaluation, Content marketing improvement were used in marketing. As a new brand, Julian.clo must aggressively market its products and increase the number of followers on social media Instagram, the celebrity Ayu Anggraini as an endorsement with followers on Instagram who has many followers, both young people in Palu City and outside Palu City. In his uploads, Julian.clo always considers the right time for resting or coming home from work, such as in the afternoon or evening because at that time many are online using social media Instagram. The celebgram used is the celebgram that has a lot of followers, making it easier for people to see every uploaded product being sold. The addition of followers and sales have increased, in terms of increased sales. Julian.clo added its marketing level from only using Gilung as a celebrity then adding Ayu Anggraini as an additional celebrity and media sponsor.